Electrical performance of monocrystalline and polycrystalline photovoltaic panels under lightning impulse voltage condition - Ahmad, Nor Izzati (2016)
Photovoltaic (PV), directly converts light from the sun into electricity and widely used in countries with high irradiation such as Malaysia. However, Malaysia is also recognised as a country prone area with lightning occurrences. Sustainable Energy Development Authority of Malaysia (SEDA) has received several complaints on damaged components and distribution boards of PV system installations and the chances of lightning strikes causing damage can be somewhat high since life span of PV systems could achieved up to 21 years or more. Therefore, this research aims to investigate the effect of lightning impulse voltage for monocrystalline and polycrystalline PV panels, the effect of temperature on the faulty PV panels and the estimation of the reduction factors of the PV panels. In this research, there are twelve PV panels in total, six monocrystalline and polycrystalline PV panels each. A PV panel was selected from each type and labelled as healthy to be the base PV panels whilst the other five PV panels of each type were taken for the lightning impulse voltage test of 100 kV, 150 kV, 200 kV, 250 kV and 300 kV each, and all are labelled as faulty. The efficiency of the PV panels were analysed through the laboratory testing for open-circuit voltage, short-circuit current, and maximum power. The findings indicated that the maximum power of healthy polycrystalline PV panel has affected about 2.88% (at 25°C) and 11.07% (up to 70°C) which is higher than healthy monocrystalline PV panel which only 1.84% (at 25°C) and 10.19% (up to 70°C). When the lightning impulse voltage is increased from 100 kV to 300 kV, the open circuit voltage and maximum power output gradually decreases for both types of PV panels demonstrating a non-linear trend for both. The percentage difference of maximum power for faulty monocrystalline is increased from 8.08% to 36.22% and for faulty polycrystalline it is increased from 0.77 % to 10.22%. Then, both types of faulty PV panels were taken for different temperature testings and the maximum power of the faulty PV panels is gradually reduced. For 300 kV (up to 70°C), the percentage difference is reduced from 9.84% to 7.11% for faulty polycrystalline PV panels. Whilst for faulty monocrystalline it is 36.22% to 32.66%, at the same trend, which the temperature affects the maximum power of both types of faulty PV panels. It was found that both healthy and faulty monocrystalline PV panels indicate the percentage difference more than 5% as stated in IEC 61215. This shown that the faulty polycrystalline PV panels performed better compared to the faulty monocrystalline PV panels. Overall, the higher the voltage stress, the degradation became severe and it becomes more serious as the faulty PV panels were exposed under high temperature. Thus, several proper forms of lightning protection system and planning for installation locations are able to be proposed in order to avoid excessive heat. Indirectly, it will reduce the cost by not having to repair the damage caused by lightning strikes as well as succeeding in investment.